Gender Role and Future Orientation in a Canadian University Population - Robinson, Anne; Page, Stewart (Canadian Journal of Counselling and Psychotherapy, 2011)
This study examines the relationship between sex. gender role, and future orientation in a Canadian university undergraduate population. Based on the previous research of Bern (1977) and colleagues, the predictive validity of the Bern Sex Role Inventory (BSRI) was specifically explored in terms of whether subjects' gender role classifications would be related to post-university career plans and life orientations. Also considered was the sex of the subject and whether the subjects were involved in romantic relationships at the time of testing. Bern's gender role classifications, of masculine, feminine, and undifferentiated subjects, did not strongly predict undergraduates' perceived future orientations in terms of preferences for a professional career as opposed to home and family involvement. Subjects generally emphasized their own career plans ahead of those of their romantic partners. Females, however, emphasized the importance of their romantic partners' careers more than males emphasized their partners' careers. Females emphasized home and family concerns more than did males. Subjects were relatively optimistic about their own personal futures, but not optimistic about the future of the country. Several implications of the findings are outlined with regard to gender role theory and counselling activities, with particular reference to women and to recent discussions about the goal of "sex role transcendence" (e.g., Stark-Adamec, Graham & Pyke, 1980).